Application of Econometrics Methods to Analyze the Impact of Climate Change on the Agricultural Sector in Developing Countries - Zirzis, Moch (Journal of Applied Econometric, 2025)
This study aims to analyze the impact of climate change on the Indonesian agricultural sector using econometric methods. Given the importance of the agricultural sector to the Indonesian economy, climate change, which affects rainfall and temperature patterns, has a significant impact on agricultural yields. The study was conducted in two provinces, West Java and South Sulawesi, each of which has different agricultural characteristics. The data used in this study included the results of in-depth interviews with farmers and policymakers, questionnaires distributed to farmers, and direct observations of agricultural practices in the field. The results show that most farmers feel the effects of climate change, especially in the uncertainty of seasons and declining crop yields. Although the government has implemented several adaptation policies, gaps still exist in their implementation. Farmers believe that existing policies are insufficient to help them cope with climate change. Therefore, this study recommends increasing farmers' access to climate adaptation technologies and more inclusive policies by involving farmers in the policy planning process that is more responsive to their needs.